Estudo da temperatura do plasma no Theta-pinch e análise de sistemas atômicos - Rezende, Dulce Cristina Jacinto (2010)
This thesis we studied the atomic emission spectra of three times ionized bromine (Br IV) and four times ionized krypton (Kr V) and correlation of energy parameters of a theta-pinch with plasma temperature, so that we measure time of flight particles that leave the plasma and the efficiency of energy transmission between the capacitor bank and the plasma. We developed a simple thermodynamic model to support the determination of temperature. Analysis of the atomic spectrum of Kr V was performed in collaboration with the Centro de Investigações Ópticas de La Plata (CIOp-Argentina) and the experimental data were obtained at the Institute of Technology of Lund (Sweden), where the thetapinch was used as light source spectroscopic. In CIOP, the experimental data were produced using a capillary discharge tube as a source of light. In the analysis of the Kr V was made the determination of all energy levels for the 4s24p5d, 4s24p6s configurations and four levels for the 4s4p24d configuration. We find the energy levels, 3P0, for the 4s24p5s 4s24p5p configurations. In this analysis were classified 91 new lines and identified 21 new energy levels for the 4s24p5d, 4s24p6s, 4s24p5s, 4s24p5p and 4s4p24d configurations. We did a review of known configurations in the literature for the three times ionized bromine. To verify the experimental data, we studied the isoelectronic sequence of the Ge I. The study of this sequence was performed to the lines for transitions between 4s24p2-4s24p4d configurations. We study the isoelectronic sequence with a ab initio calculation and experimental data found in literature. This thesis we present the possible values experimental for Br IV. We determined temperature of the plasma formed in the theta-pinch. Using two types of probe, a piezoelectric sensor and a resistive. We also developed a semiempirical expression, which was described in terms of energy parameters of the thetapinch, to determine plasma temperature. The results of the plasma temperature were compared. The theoretical support of this thesis was obtained with a program developed by Professor Robert D. Cowan for numerical calculations of atomic structures.